Series Expansion of Exponential and LogarithmicFunctionsLeonhard Euler, the great Swiss mathematician introduced and named...
ex+4 = e4(1+               + +.............)        ex = 1 +              + +.............        e-x = 1 -              -...
(vi)       Example 3. Find the sum of the following to infinity:(vii)      (i)                                   (ii)(viii...
= 2e5e +4e = 11e.                              [ assume Tn = an2+bn+c , put n=2,3,4 and by solving eqns. We   will get a= ...
For (iv) we get (x2-y2)+1/2!(x4-y4)+1/3!(x6-y6)+..... =(   - 1)- (   – 1) =         .                                     ...
xThe graph of y = e is upward-sloping, and increases faster as x increases. The graph alwayslies above the x-axis but can ...
Loge3 = 2[1/2+(1/2)3/3+(1/2)5/5+........] , by putting (1+x)/(1-x)=3 it givesx=1/2, similarly we can do for log4,log5 and ...
5. log(1+x).(1+x)-1 =( x -                     + .......)(1-x+x2-x3+x4-x5+.....)6. R.H.S. = log(1+                        ...
2. L.H.S. = log[(1+x)(1+2x)] = log(1+x)+log(1+2x) = R.H.S.   3. L.H.S. = log{x(1+a/x)}-log{x(1-x/a)} = log(1+x/a) – log(1-...
Series expansion of exponential and logarithmic functions
Upcoming SlideShare
Loading in...5
×

Series expansion of exponential and logarithmic functions

23,363

Published on

Series expansion of exponential and logarithmic functions for entrance exams.

0 Comments
3 Likes
Statistics
Notes
  • Be the first to comment

No Downloads
Views
Total Views
23,363
On Slideshare
0
From Embeds
0
Number of Embeds
2
Actions
Shares
0
Downloads
193
Comments
0
Likes
3
Embeds 0
No embeds

No notes for slide

Transcript of "Series expansion of exponential and logarithmic functions"

  1. 1. Series Expansion of Exponential and LogarithmicFunctionsLeonhard Euler, the great Swiss mathematician introduced and named thenumber e in his calculus text in 1748.ex = 1+ + +.............Putting x=1 in there, we get:e1=1+1/1!+1/2!+1/3!+....which givese=1+1+.5+.17+...so e is approximately 2.67or 2< e< 3 and the value of e2 = 7.3 by using exp. Series.e3x = 1+ + +.............which simplifies to:e3x = 1+3x+9x2/2!+27x3/3!+81x4/4!+.....To write ex+2 as a series, it is best to rewrite ex+2 as ex. e2 so:ex+2 = e2(1+ + +.............)This is true for any constant c in ex+c, try writing down the first four terms ofthe series for ex+4,The series for ex+4Here is start of the series for ex again:ex = 1+ + +.............Now recall that ex+4 is the same as ex.e4, so we just need to multiply the seriesfor ex by the number e4. That gives us:
  2. 2. ex+4 = e4(1+ + +.............) ex = 1 + + +............. e-x = 1 - - +............. [coefft. Of xn ix (-1)n/n!] by adding & subtracting above two series , we get = 1+ x2/2! +x4/4!+........... and =x+ x3/3! +x5/5!+........... = = and = = Some important points should be noticed =e = (ii) = e–1, =e–2 (iii) =e–1, =e–2= Example 1. Find the sum of the following to infinity (i) 1/1!+2/2!+3/3!+..... (ii) x/1!+2x2/2!+3x3/3!+..... Solution: (i) 1/1!+2/2!+3/3!+..... = = =e (ii) = x( ) = xex . Example2. Find the sum of the following to infinity:(i) (i) (ii)(ii)(iii) Solution: (i) = = = = + =e+e=2e.(iv) (ii) = =x( ) + x2 ( ) = xex + x2 ex .(v)
  3. 3. (vi) Example 3. Find the sum of the following to infinity:(vii) (i) (ii)(viii)(ix) Solution: (i) = = = = +(x) = + + = + +(xi) = e + 3e + e = 5e.(xii) (ii) = = + +x = (x3+3x2+x)ex Some questions with hints : Q.1 Find the sum of following (i) x + + +........ (ii) 1 + + +........ Solution: (i) Tn = = = ½( ) , Sn = ½( (2xex + x2ex) [ by example 1 & 2 we can find (ii) answer is ½(2e+e)= 3e/2] Q.2 find the sum of the following series: (i) (ii) (iii) + + +........ (iv) 12/2! + 28/3! + 50/4!+78/5!+.......... (v) 2/1! + 6/2! + 12/3!+20/4!+......... (vi) 1+ 3/2! + 6/3! +10/4! +....... Solution: (i) = = = -2 + [by above examples ] 2e-1-2e+2+e-2 = e-1. = + = 5e +2e = 7e. = = +5 +4
  4. 4. = 2e5e +4e = 11e. [ assume Tn = an2+bn+c , put n=2,3,4 and by solving eqns. We will get a= 3, b=1 & c=-2] by above part (i) we get, 3(2e-1)+(e-1) -2(e-2) = 5e. = [assume Tn = an2+bn+c , put n=1,2,3 and by solving eqns. We will get a= 1, b=1 & c=0] by above part (ii) we get, 2e+e = 3e. [assume Tn = an2+bn+c , put n=1,2,3 and by solving eqns. We will get a= 1/2, b=1/2 & c=0] by above part (ii) we get, ½ (2e+e) = 3e/2. 3 find the sum of (i) (ii) if S = , find 2S. : (i) [ by using C(n,2) = n(n-1)/2! And by above results ] −2) = e2 – 1. (iii) S = =1/2 = ½ e3 . 4. (i) If = B0+B1x+B2x2+.....+Bnxn , then find the value of (Bn – Bn-1). find the sum of 2/3!+ 4/5! +6/7!+..... (iii) 2/1! +4/3!+6/5!+...... find the sum of (x+y)(x-y) +1/2!(x+y)(x-y)(x2+y2)+1/3!(x+y)(x-y)(x4+y4+x2y2)+...... : (i) ex(1-x)-1 = B0+B1x+B2x2+.....+Bnxn 1 + x/1! + x2/2! + x3/3!+......+xn-1/(n-1)!+xn/n!+....)(1+x+x2+x3+....+xn- 1 n +x +...) B0+B1x+B2x2+.....+Bnxn Coeffts. Of xn and xn-1 on the both sides, we get 1/n!+1/(n-1)!+....+1/2!+1/1!=1=Bn 1(n-1)!+1/(n-2)!+....+1/2!+1/1!+1=Bn-1. Therefore Bn – Bn-1 = 1/n!.For (ii) & (iii) ,we will take help of above results and , then add & -1subtract 1 in Nr. Accordingly .[answer of (ii) e (iii) e]
  5. 5. For (iv) we get (x2-y2)+1/2!(x4-y4)+1/3!(x6-y6)+..... =( - 1)- ( – 1) = . e= [by using binomialtheorem = 1+n. + +.....] = 1+1+1/2!+1/3!+..... as 1/n, 2/n, 3/n ...=0 as n .Let a >0, then for all real values of x,ax = 1+ x(logea) + x2/2! (logea)2 +..........how we will you get this series, put x=cx in exp. Series , thenecx = 1+cx +(cx)2/2! + .......... = 1+ x(logea) + x2/2! (logea)2 +..........[let ec =a it implies c= logea & ecx = (ec)x = ax.]
  6. 6. xThe graph of y = e is upward-sloping, and increases faster as x increases. The graph alwayslies above the x-axis but can get arbitrarily close to it for negative x; thus, the x-axis is ahorizontal asymptote. The slope of the tangent to the graph at each point is equal toits y coordinate at that point. The inverse function is the natural logarithm ln(x); because ofthis, refer to the exponential function as the antilogarithm.The natural logarithm function, if considered as a real-valued function of a realvariable, is the inverse function of the exponential function, leading to the identities: , ,put x=1 in loge(1+x) then loge2= 1-1/2+1/3-1/4+..... is valid. Natural Log Series
  7. 7. Loge3 = 2[1/2+(1/2)3/3+(1/2)5/5+........] , by putting (1+x)/(1-x)=3 it givesx=1/2, similarly we can do for log4,log5 and so on......We know that = 2(x + .............)=1+0.083+0.012+...=1.098 0.61< loge2 < o.76 [as we can write loge2= (1-1/2)+(1/3-1/4)+..... >0.61 andloge2= 1-(1/2-1/3)-(1/4-1/5)-.....<0.76 we can write log2 < 1 < log3Some examples:1. If y = x- x2/2+x3/3-x4/4+.....and if |x|<1, prove that x=y+y2/2!+y3/3!+....2. Prove that ...........has the same sum as the series ........... prove that 2 logx – log(x+1) – log(x-1) = ........... . If y > 0 , then prove that logy = 2 { +.........}And hence find the value of log2 to three places of decimals.5. prove that for |x| <1, =x- ..........6. if are the roots of x2 – px +q=0, prove thatlog(1+px+qx2) = ( )x-(Solution: 1. y=log(1+x) it implies ey = 1+x , write exponential series. 2.Put x = 1/(n+1) it gives x+ +..... = - (- x- +.....)= - log(1-x) Put x=1/(1+n), we get - = = ...........3. L.H.S. = =- = ...........[by using laws of logarithmics]4. Put x = , then R.H.S. = 2(x + .............)= = logy, then put y=2 in question it gives 0.693= log2.
  8. 8. 5. log(1+x).(1+x)-1 =( x - + .......)(1-x+x2-x3+x4-x5+.....)6. R.H.S. = log(1+ = log(1+( ) = log(1+px+qx2) Some important questions with hints: Q.1 Prove that = 2( + +....) Q.2 prove that for |x| < ½ , log(1+3x+2x2) = 3x - ..... Q.3 prove that log(x+a) – log(x-a) = 2( +.......) Q.4 prove that = logba. Q.5 prove that = [1 - ...........] Q.6 if x2y = (2x-y) and |x| <1, prove that (y+ y3/3+y5/5+.....) = 2( x+x3/3+x5/5+.....) Q.7 prove that (i) +........= ½ log2. (ii) +.......= log2. (iii) +........= 2-2log2. Q.8 Find the sum of (i) +........... (ii) +......... (iii) +............. (iv) - ......... Answers with hints 1. = (1+x)log(1+x)+(1-x)log(1-x) = [log(1+x)+log(1-x)]+ x[log(1+x)+log(1-x)] = -2(x2/2+x4/4+x6/6+....) + 2x (x+x3/3+x5/5+....) =2( + +....)
  9. 9. 2. L.H.S. = log[(1+x)(1+2x)] = log(1+x)+log(1+2x) = R.H.S. 3. L.H.S. = log{x(1+a/x)}-log{x(1-x/a)} = log(1+x/a) – log(1-x/a) [Use use series of log(1+x) & log(1-x)] 4. Let x=a-1 & y=b-1, then L.H.S. becomes loge(1+x)/loge(1+y)=logea/logeb= logba 5. Put x = 1/(n+1), we get ( .......) =[1-(1-1/2)x – (1/2-1/3)x2-(1/3- 1/4)x3-.....] =[( 1 + .......) - ( x + +.......)] [1/x( x + .......) - ( x + ......)]=-1/xlog(1-x)+log(1-x), put the value of x ,it becomes nlog(1+1/n)=R.H.S. 6. L.H.S. =y(x2+1) =2x it implies y= 2x/(x2+1) , we get = by taking log on the both sides & use log (1+x)/(1-x). 7. (i) put x=1/3 ,L.H.S. & use this result 2(x + .............)=(ii)nth term = , n=1,2,3.... ( by partial fraction which is used forintegration) it can be written as 1= A(2n) + B(2n-1), find A & B by putting n=o &n=1/2,so we get A=1,B =-1, then sum to n terms becomes =1-1/2+1/3-1/4+.......=log2. (iii) nth term = , n=1,2,3.... ( by partial fraction which is used for integration) it can be written as 1= A(2n+1) + B(n), find A & B by putting n=o & n=-1/2,so we get A=1,B =-2, then sum to n terms becomes =2[1/2-1/3+1/4-1/5+.......]=-2 [-1/2+1/3-1/4+1/5+.......] =-2 [log2-1]= R.H.S. Q.8 (i) nth term = , n=1,2,3....same as above method we get A= 2, B=-3 &C=1 sum = = = 2(1-1/2+1/3-1/4+....)+(-1/2+1/3-1/4+.......)=3log2-1. (ii) nth term = , n=1,2,3....same as above method we get A= 1/2, B=-1 &C=1/2 sum = = = ½ {(1-1/2+1/3-1/4+....)+(-1/2+1/3-1/4+.......)}=log2-1/2.(iii)put x= 1/5 , sum = = = - (1+x) – = – )– 1= (1-x)-1 + log(1-x) – 1= by putting x=1/5.(iv)L.H.S. = }+ }=1/2{log(1+1/2)+log(1+1/3)} =1/2log(3/2X4/3)=1/2log2.

×